Career Paths and Educational Effectiveness: A Tracer Study of Indonesian Literature Alumni at Universitas Alkhairaat Palu - Rizky Anugrah Putra; Syamsuddin; Suparni; Mu'jizat; Rasuna Rasid Talib; Sayama Malabar (Applied Linguistics: Innovative Approaches and Emerging Trends, 2025)
This study examines the alignment between the employment of alumni from the Indonesian Literature Study Program at Universitas Alkhairaat and the field of knowledge they pursued. To achieve these goals, the researcher conducted a qualitative descriptive analysis of alumni who graduated in the past two years, using an online tracer study questionnaire. The results were presented in chart to facilitate the understanding of quantitative data. The findings revealed that most alumni from the program have entered the workforce. 78% of participants stated that the courses offered in the program were relevant to their current jobs, while 22% found no relevance. The researcher concluded that this mismatch could be attributed to the competitive job market and workforce saturation, leading employers to seek graduates with specialized skills and unique value.